Jerash Governorate Farmers Adopt Integrated Management Methods to Combat Fruit Tree Diseases - Al-Ameiri, Nofal S.; Bdour, Mohammed A. (Jordan Journal of Agricultural Sciences, 2022)
This study aimed to measure the adoption of integrated pest management techniques by fruit tree growers in Jerash Province of Jordan for diseases affecting their tree crops and to develop future visions for their development. The study was based on the collection of preliminary data via interview, using the questionnaire tool, and took a random sample of fruit tree farms from a total area of 3,822 dunums constituting 5.5% of the total area planted with fruit trees. This area is exploited by 70 growers distributed in the whole province. The results of the present study indicated that 88% of the respondents are educated and approximately 65.8% of growers have secondary and university graduates. Respondents used regularly the IPM was only 7.1%. The study showed that the most important diseases affecting fruit trees were fungal diseases, especially powdery mildew, leaves curl, and eyes of peacocks, which are considered the most dangerous diseases of trees limiting production quantities and more expensive as a result of repeated application of pesticides. The five-grade Lekert scale was used for evaluation; "always" was given five degrees and "never" represent one degree for the positive answers, while the scoring was reversible to the negative responses; "never" was given one score, and "always "was given five degrees. This scale covered twenty-four actions done by the growers to protect their trees. Alpha Kronbach Coefficient was 0.78, reflecting the internal consistency of the study scale. In the current study descriptive statistics methods such as repetitions, percentages and arithmetic averages, and standard deviation were used to analyze the data statistically. According to Leckert scale, items 5-21 gave a mathematical average of 1.96-3.5, and 35.7% of the respondents know what the concept of integrated control is? and this shows that the respondents did not use any of the methods of IPM. 35.7% of the information about IPM is obtained by the farmer from the Ministry of Agriculture, the Colleges of Agriculture, and the NNARC. This study recommends new legislation to regulate the effectiveness, impact, and duration of pesticide use, and support the use of IPM inputs to combat the development of a national guidance program to adopt the use of IPM across Jordan and to create marketing incentives for IPM produced by the IPM-adopted growers.